Synthesis and characterization of compounds derived from 2-Cyanopyridine - Fulwa, Vijendra Kumar (My University, 2012)
Chapter 1 summarizes the literature reports that use 2-cyanopyridine, specifically, for synthesis of heterocycles has been reviewed. Chapter 2 describes the synthesis and characterization of copper(II) coordination polymers using two amidoximes viz., pyridine-2-amidoxime and pyrazine-2-amidoxime. In addition, a linear trinuclear complex synthesized using the latter has been described. Chapter 3 describes the synthesis of 2,4,5-tris(pyridyl)imidazoles and N-(3-(pyridil) imidazo[1,5-a]pyridine) picolinamidines using 2-cyanopyridine and picolylamines. Plausible mechanism for the formation of these compounds is composed. Chapter 4 describes the reaction of 2-cyanopyridine, hydrazine hydrate and pyridinecarboxaldehydes. The products isolated include 3,5-di(2-pyridyl)-1,2,4-triazole-1-(3-(2-pyridyl)-5-(pyridyl)-1,2,4-triazolyl)-3-(pyridyl)imidazo [1,5-a]pyridine and1-((pyridyl)methanimine)-3-(pyridyl)imidazo[1,5-a]pyridine. Chapter 5 describes the synthesis and characterization of 3-substituted imidazo[1,5-a] pyridines having N-picolinamidin-2-yl group at 1-position. This was achieved by reacting one equivalent of aldehyde and two equivalents of 2-cyanopyridine.
Manivannan, V.
Keywords: CHEMISTRY